Three Previously Undescribed Chlorophenyl Glycosides from the Bulbs of Lilium regale. Issue 10 (2nd September 2021) - Yan, Jie; Guo, Wenxiu; Zhou, Lanyu; Guo, Dale; Pei, Jin; Deng, Yun; Zheng, Haoyuan; Liu, Ding; Xie, Xiaofang; Peng, Cheng
Abstract: Three previously undescribed chlorophenyl glycosides, (2, 4, 6‐trichloro‐3‐hydroxy‐5‐methoxyphenyl)methyl β‐D‐glucopyranoside (1 ), (2, 4‐dichloro‐3, 5‐dimethoxyphenyl)methyl 6‐ O ‐β‐D‐glucopyranosyl‐β‐D‐glucopyranoside (2 ) and 4‐chloro‐3‐methoxy‐5‐methylphenyl 6‐ O ‐(6‐deoxy‐β‐L‐mannopyranosyl)‐β‐D‐glucopyranoside (3 ) were obtained from Lilium regale . The absolute configurations of these new finds were elucidated by comprehensive analyses of spectroscopic data combined with acid hydrolysis derivatization. (2, 4‐dichloro‐3, 5‐dimethoxyphenyl)methyl 6‐ O ‐β‐D‐glucopyranosyl‐β‐D‐glucopyranoside (2 ) can inhibit the proliferation of lung carcinoma A549 cells with an IC50 value of 29 μΜ. Abstract :